Defragmentation of construction holes in students with high mathematical ability: Addressing “skipping steps” errors using scaffolding - Liny Mardhiyatirrahmah; Dewi Rosikhoh (Universitas Muhammadiyah Surakarta, 2026)
High-ability students generally excel in mathematics but frequently make